Myocardial expression of connexin 43 in cats with hypertrophic and restrictive cardiomyopathy phenotype - Dmitrij Oleynikov (Open Veterinary Journal)
Background: In humans and cats hypertrophic cardiomyopathy (HCM) is a cause of sudden cardiac death. This is usually associated with arrhythmias, based on myocardial fibrosis and electric impulse propagation disturbances. Restrictive cardiomyopathy (RCM) is a cardiomyopathy associated with excessive fibrosis which is predisposed to arrhythmic episodes. Electric coupling in the myocardium is based on His-Purkinje system and cardiomyocytes cell-to-cell contacts. Cell connection is based on gap junctions and their structural proteins - connexins. Today there is a lack of information in literature regarding these functional units and their distribution in cats.